Impact of delayed feedback of arbitrary duration in self-pulsations of a CO2 laser - Junges, Leandro; Gallas, Jason (Journal of the Optical Society of America, 2016)
feedback. Such a laser roughly displays three operational intervals of stability, which we characterize using highresolution stability charts and a video. Contrary to current belief, we find delays smaller than ∼1 μs to strongly “clean complexity,” namely, to prevent chaos and periodic pulsations with many spikes. In contrast, complex pulsations and chaos are significantly enhanced for τ > 1 μs. In this range, one finds a complex alternation of periodic and chaotic phases, which are sensitive to the delay duration. © 2016 Optical Society of America
Keywords: Lasers; carbn dioxide; nonlinear optics; Instabilities and chaos